2012
DOI: 10.3390/fi4030776
|View full text |Cite
|
Sign up to set email alerts
|

Adapted User-Centered Design: A Strategy for the Higher User Acceptance of Innovative e-Health Services

Abstract: Abstract:Being familiar with all the benefits of e-Health and the strategic plan for the Slovenian health sector's informatization, Telekom Slovenia and the Faculty of Medicine from the University of Maribor, along with other partners, have initiated an e-Health project. The project group is developing various e-Health services that are based on modern ICT (information and communications technology) solutions and will be available on several screens. In order to meet the users' needs and expectations and, cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…It is also technology-agnostic, meaning that it is suitable for use with a variety of products, ranging from hardware to mobile apps, which are both aspects of the system examined in this study. Furthermore, SUS has been previously used with telehealth systems [29][30][31]. The method is also non-proprietary, as well as easy and low-cost to implement.…”
mentioning
confidence: 99%
“…It is also technology-agnostic, meaning that it is suitable for use with a variety of products, ranging from hardware to mobile apps, which are both aspects of the system examined in this study. Furthermore, SUS has been previously used with telehealth systems [29][30][31]. The method is also non-proprietary, as well as easy and low-cost to implement.…”
mentioning
confidence: 99%
“…By using open‐ended questions, respondents are allowed to innovate freely and propose ideas that go beyond specific services; hence, the answers can also be useful for informing the development of multiple types of services. As it has been found that lack of resources hinder cooperation between end‐users and software developers (Rytkönen, Kinnunen & Martikainen, 2022), and user‐centered design approaches usually include several phases such as planning, designing, testing and evaluating, requesting longer time spans and hence more resources (Cornet et al, 2020; Gould & Lewis, 1985; Stojmenova, Imperl, Žohar & Dinevski, 2012; van Velsen, Ludden, & Grünloh, 2022), the option of including open‐ended questions in larger studies related to eHealth information behavior, can be a cost‐effective way to provide developers with useful feedback. The approach can be termed as a form of citizen science (van Velsen, Ludden, & Grünloh, 2022) with a major benefit of not requiring a recruiting of end‐users at certain points of time at certain places, or the effort of testing existing services thoroughly multiple times (Cornet et al, 2020; Gould & Lewis, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Conventional participatory design methods and techniques may be tailored to account for a diversity of different user characteristics, languages, community cultures, environments, and motivations [22]. To ensure representative results are obtained, researchers should adapt participatory design methods to ensure they are relevant and feasible in the context of their target population, with close attention to cultural differences in engagement with technology.…”
Section: Pillar 1: Inclusive Participatory Designmentioning
confidence: 99%